2011
DOI: 10.1111/j.1471-4159.2010.07151.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity regulates expression of tyrosine hydroxylase in adult mouse substantia nigra pars compacta neurons

Abstract: Dysfunctional dopaminergic (DAergic) neurotransmission between the substantia nigra pars compacta (SNc) and the dorsal striatum (the nigrostriatal pathway) causes several prominent movement disorders (e.g. the motor symptoms of Parkinson's disease, dystonias and dyskinesias). Both too much and too little DA signalling can be problematic and nigrostriatal DAergic transmission is maintained at normal levels by several homeostatic mechanisms acting over timescales of milliseconds to weeks: e.g. binding of DA to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
87
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 62 publications
13
87
0
2
Order By: Relevance
“…278 intraventricular administration of a GABA A receptor agonist (Soriano et al 1997, Yamada et al 1996; SNc TH mRNA is elevated followed systemic administration of nicotine or α-7 nicotinic acetylcholine receptor agonists (Serova & Sabban 2002); and we recently reported that the number of SNc TH+ cells in adult mice can be increased or decreased by direct brain infusions of drugs targeting SNc neuronal activity (Aumann et al 2011, Aumann et al 2008. These data are consistent with the possibility that the DA phenotype of adult SNc neurons can be gained or lost in an activity-dependent way.…”
supporting
confidence: 75%
See 4 more Smart Citations
“…278 intraventricular administration of a GABA A receptor agonist (Soriano et al 1997, Yamada et al 1996; SNc TH mRNA is elevated followed systemic administration of nicotine or α-7 nicotinic acetylcholine receptor agonists (Serova & Sabban 2002); and we recently reported that the number of SNc TH+ cells in adult mice can be increased or decreased by direct brain infusions of drugs targeting SNc neuronal activity (Aumann et al 2011, Aumann et al 2008. These data are consistent with the possibility that the DA phenotype of adult SNc neurons can be gained or lost in an activity-dependent way.…”
supporting
confidence: 75%
“…replenishing SNc DA cells by DA phenotype recruitment). We also note that the doses of riluzole used so far in clinical trials for PD have all been relatively low (around 3μM) rather than the 30μM, which we have shown increases the number of SNc TH+ cells in normal mice (Aumann et al 2011). Therefore, any restorative benefit of riluzole through DA phenotype recruitment may have been missed.…”
Section: Riluzole In Micementioning
confidence: 80%
See 3 more Smart Citations